Names of Jesus in Mark’s story - Y. Dreyer (In die Skriflig, 2001)
Mark as narrator treats the concept “Messiah” as a description of Jesus’ identity, but this alone does not suffice: the title “Son of God” is added in order to describe Jesus’ identity more fully. According to Mark it is not the Twelve but some of the other followers who praise Jesus with the title of the “Blessed One who comes in the name of the Kyrios”. “Messiah” is the title the disciples give to Jesus, but the “narrated Jesus” subordinates the title “Messiah” to the title “Kyrios”. The aim of this article is to focus on Mark as narrative. The article argues that all events are presented from one perspective, that is the perspective of Jesus. This perspective is narrated by using names of Jesus. The article focuses on these names as used in the Gospel of Mark.